Microbial applications. Vol. 1, - Kalia, Vipin Chandra; Kumar, Prasun (Springer, 2017)
This contributed volume sheds new light on waste management and the production of biofuels. The authors share insights into microbial applications to meet the challenges of environmental pollution and the ever-growing need for renewable energy. They also explain how healthy and balanced ecosystems can be created and maintained using strategies ranging from oil biodegration and detoxification of azo dyes to biofouling. In addition, the book illustrates how the metabolic abilities of microorganisms can be used in microbial fuel-cell technologies or for the production of biohydrogen. It inspires young researchers and experienced scientists in the field of microbiology to explore the application of green biotechnology for bioremediation and the production of energy, which will be one of the central topics for future generations.
Keywords: Microbial biotechnology.; elektronické knihy; electronic books